Perancangan Desain Kemasan Sebagai Media Peningkatan Brand Awareness Janus Coffee & Roastery - Bhakti, Aditya Dwi Putra; Sungkono, Fandy Pratama (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2023)
Janus Coffee & Roastery is a coffee roastery located in Batu City Square and has been established since 2018. The background for this research is that Janus has not focused too much on designing packaging designs, on the other hand, packaging design has strong potential in efforts to increase product brand awareness. Therefore, the purpose of this research is to design packaging design for Janus Coffee & Roastery in an effort to increase brand awareness. This design uses a qualitative and descriptive approach. Data collection techniques through observation, interviews, and literature study were analyzed using the SWOT and USP methods. The results of this creative design are packaging illustrations, brand colors, brand patterns, and typography. The end result of packaging design is applied to media such as coffee bags, drip bags, drip bag boxes, shopping bags, plastic bags, and coffee cups which are adjusted in terms of safety, ergonomics (comfort), and experience (experience).